Aplicação da ferramenta SERVQUAL na avaliação da qualidade dos serviços de saúde em uma maternidade de Manaus-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
Preliminarily meets demonstrate that the concept of quality encompasses the various dimensions involved in this study. Aiming to apply the SERVQUAL tool for assessing the quality of health services at the Maternity of the new city Mrs.Nazira Daou, based on analyze the flow of processes and maternity services; Check for standardized services; Describe the five dimensions: tangibility, reliability, sensitivity, Security and Empathy, the SERVQUAL model; Analyze the results of the dimensions of the model. The study answers the problem "Women mothers express satisfaction with the health service received the motherhood"? Research approved as CEP / UFAM CAEE No. 43765615.7.0000.5020, the collection was carried out through a direct approach to the bedside, with application of closed and validated questionnaire containing 10 dimensions totaling 18 issues, parameterized on Likert scale the sample population was 100 puerperal women (immediate postpartum), the qualitative and quantitative type research. In the construction of the graphic was used Excel INFO 7.0 program; For the study of validation was applied Alpha Crombach and, according to the respondents the total metric for each dimension: 238 responses with negative concept of Likert (1 and 2); 1,275 on the positive concept of Likert (4:05) and 287 remained indifferent to the concept (3) totaling 1,800 responses collected. For positive assessment goal was all result> .80. The study was the following: Access-positive and 86% negative and 19% Indifferent 19%; Flexibility- Positive and negative 72% and 6% Indifferent 22%; Availability- Positive 57% and negative 25% Indifferent 18% (question 1), Positive 15% and negative 54% Indifferent 31% (question 2); Positive 20% and negative 54% Indifferent 26% (question 3); Communication- Positivo70% and negative 11% and 19% Indifferent; Agility- Positive 78.6% and negative 7.8% and 13.6% Indifferent; Courtesy Positive 90% and negative 21% and 8% Indifferent (Question 1), positive and negative 86% and 2% Indifferent 12% (question 2), Positive 90% and negative 1% and 9% Indifferent (question 3); Competence- Positive 91% and negative 1% and 8% Indifferent (Question 1), positive and negative 92% and 0% Indifferent 8% (question 2); Security- Positive 66% and negative 20% and 14% Indifferent (Question 1) and (Question 2) Positive 54% and negative 28% and 18% Indifferent .The access dimensions, courtesy and competence obtained Normal status showing consistency. Already inconsistent dimensions showed failure to validate and among them are comfort, flexibility, communication and mobility; the weak point was the access dimension, although Normal status, which predicts a good satisfaction rating when validated been shown to unacceptable coefficient. However the construct obtained a coefficient> .8 which predicts GOOD construct. The study showed that although the respondents have expressed satisfaction with the services received yet there are specific events that require a more direct realistic assessment into this universe, a fact that encouraged the author to reflect on the implementation of appropriate and specific tool for this activity. Founded this the author makes the proposition of an adapted tool called SERVQUAL-HEALTH with design to motivate improvements in this segment.
Keywords: Qualidade; Serviqual; Serviços; Maternidade; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO